2020
DOI: 10.1039/d0dt00683a
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure-assisted charge transfer in α-Fe2O3/g-C3N4 heterojunctions for efficient and highly stable photoelectrochemical water splitting

Abstract: Development of semiconductor heterojunction is a promising and yet challenging strategy to boost the performance of photoelectrochemical (PEC) water splitting. This paper describes the fabrication of heterojunction photoanode by coupling...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Consequently, α-Fe 2 O 3 -modified g-C 3 N 4 is considered as a highlight approach to create low-cost, efficient, eco-friendly environmental photocatalysts. Many reports showed that composite materials of α-Fe 2 O 3 /g-C 3 N 4 Z-scheme photocatalysts remarkably enhance the photocatalytic efficiency in water splitting for H 2 generation, CO 2 reduction, , Cr­(VI) and As removal, , organic dye degradation, NO oxidation, and so forth. In general, previous studies on Fe 2 O 3 /g-C 3 N 4 nanocomposites indicated that combining these two materials created a Z-scheme photocatalyst, which led to superior charge transportation and reduced recombination, leading to improved photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, α-Fe 2 O 3 -modified g-C 3 N 4 is considered as a highlight approach to create low-cost, efficient, eco-friendly environmental photocatalysts. Many reports showed that composite materials of α-Fe 2 O 3 /g-C 3 N 4 Z-scheme photocatalysts remarkably enhance the photocatalytic efficiency in water splitting for H 2 generation, CO 2 reduction, , Cr­(VI) and As removal, , organic dye degradation, NO oxidation, and so forth. In general, previous studies on Fe 2 O 3 /g-C 3 N 4 nanocomposites indicated that combining these two materials created a Z-scheme photocatalyst, which led to superior charge transportation and reduced recombination, leading to improved photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…presented the CO 2 photoreduction performance with the Z-scheme mechanism of Fe 2 O 3 /g-C 3 N 4 , which portrays our reported mechanism. 21 Furthermore, degradation of tetracycline, 25 4-nitrophenol degradation, 33 photoelectrochemical water splitting, 73 CO 2 reduction, 22,44 methanol oxidation, 74 bactericidal performance, 75 and H 2 generation 76 applications have been reported in relation to our suggested mechanism of Fe 2 O 3 /g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 54%
“…S6†), where longer transient time implies lower recombination rate. According to the calculation method described in our previous work, 50 TiO 2 -500 reveals the longest transient decay time (0.086 s), followed by TiO 2 -600 (0.070 s) and TiO 2 -400 (0.054 s).…”
Section: Resultsmentioning
confidence: 96%